Decomposition of Deep Eutectic Solvent Aids Metals Extraction in Lithium‐Ion Batteries Recycling. Issue 18 (10th August 2022) - Schiavi, Pier Giorgio; Altimari, Pietro; Sturabotti, Elisa; Giacomo Marrani, Andrea; Simonetti, Giulia; Pagnanelli, Francesca
Abstract: The application of deep eutectic solvents (DESs) to dissolve metal oxides in lithium‐ion batteries (LIBs) recycling represents a green technological alternative to the mineral acids employed in hydrometallurgical recycling processes. However, DESs are much more expensive than mineral acids and must be reused to ensure economic feasibility of LIB recycling. To evaluate DES reusability, the role of the choline chloride‐ethylene glycol DES decomposition products on metal oxides dissolution was investigated. The temperatures generally applied to carry on this DES leaching induced the formation of decomposition products that ultimately improved the ability to dissolve LIB metal oxides. The characterization of DES decomposition products revealed that the improved metal dissolution was mainly determined by the formation of Cl3 −, which was proposed to play a pivotal role in the oxidative dissolution of LIB metal oxides. Abstract : Finding a (dis)solution : Thermal decomposition of chloride‐ethylene glycol deep eutectic solvent taking place during the leaching of waste Li‐ion batteries drives the dissolution of metals through an oxidative leaching mechanism enabled by the formation of Cl3 − .